Effect of Different Amount of Comminuted Goat Meat Added on The Quality of Crackers - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT Crackers (Kcniprik) are popular snack food in Indonesia and other ASEAN countries and usually the tradisional crackers arc prepared by forming a dough from a mixture of flour, comminuted fish or prawn and water, The dough of steamed, thin sliced and dried before deep frying, The possibility of using goat meat instead of fish or prawn in the production of crackers has been studied. Goat meat crackers %cere formulated with 10,20,30,40,50 and 61) percents comminuted goat